“Ich wollte ein paar heilige Kühe schlachten.” Notes on Cancer in Hildegard Knef’s Das Ureil oder Der Gegenmensch (1975) and Its Reception - LEÓN-VILLAGRÁ, Diego (Anafora, 2023)
Hildegard Knef’s Das Urteil oder Der Gegenmensch (1975) is rarely noticed by literary and cultural studies on illness narratives, although this bestseller and highly polarizing media event was one of the first autobiographical cancer narratives in German-speaking countries, and an eminent pre-text of the conjunction of autobiographical illness narratives since the late 1970s. Autobiographical writing in Das Urteil reflects a self-technique to create a coherent and updated self-image in the case of existential illness. At the same time, the book focuses on a distinct criticism of the health system, the incapacitation of patients, the “war jargon” in the medical system, and the semantics of cancer in public discourse, which as the postulation for an informed patient induces a popularization of medical knowledge and vocabulary. In the context of the critically recognized expansion of cultural discourses on illness and death since the mid-1970s, the article highlights the reception history of Knef’s Das Urteil, also published in English under the Title The Verdict in 1975. Furthermore, the article relates the text to Susan Sontag’s famous essay Illness as a Metaphor (1977), in which Sontag systematically analyzed precisely those elements which Knef presented in her personal report two years earlier: the metaphors, narratives and stigma of cancer, especially in the medical system. This shows the extent to which Das Urteil, despite its extremely critical reception history, contributed to the destigmatization of cancer in public.